From Cold War to hot peace UN interventions 1947-1994 - Parsons, Anthony, 1922- (London : M. Joseph, 1995)
SCOTT (copy 1): From the John Holmes Library Collection.
Includes bibliographical references.
Keywords: United Nations. -- History; United Nations. -- History; World politics -- 1945-